STRATEGI PEMANFAATAN E-COMMERCE UNTUK MENINGKATKAN DAYA SAING UMKM: SEBUAH TINJAUAN SISTEMATIS - Basriyani, Anna; Fitriyani Panggabean; Mhd. Safwan Koto; Safran Matondang (Cattleya Darmaya Fortuna, 2026)
This systematic literature review aims to explore e-commerce utilization approaches that contribute to strengthening the competitiveness of Small and Medium Enterprises (SMEs).The discussion includes an analysis of driving The review demonstrates that the effectiveness of e-commerce adoption is shaped by digital preparedness, policy backing, and resource capabilities.The study concludes that an integrated approach combining technological, organizational, and environmental aspects is necessary to optimize SME competitiveness through e-commerce.